Using the Picture Exchange Communication System With Students With Visual Impairment. (July 2014) - Ivy, Sarah E.; Hatton, Deborah D.; Hooper, Jonathan D.
Students with visual impairment (VI) were taught to request using the Picture Exchange Communication System (PECS) and tangible symbols. Participants were four males with additional disabilities, 5 to 11 years old, who had little to no functional vision. A functional relation between PECS Phase 1 and requesting was established using a multiple baseline single subject design. All students learned to request independently within 7 to 14 sessions in Phase 1. Students maintained requesting above criterion for 1 to 5 months. All students generalized requesting to a new communication partner (CP); however, only two students reached criterion during generalization sessions. Two students learned to seek out a CP 5 feet away to request; however, no functional relation was established for Phase 2. More research is needed to establish PECS as an evidence-based practice for children with VI.